2018
DOI: 10.3390/jcm7100331
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Hemodialysis or Hemodiafiltration: When One Size Does Not Fit All the Proposal of a Personalized Approach Based on Comorbidity and Nutritional Status

Abstract: There is no simple way to prescribe hemodialysis. Changes in the dialysis population, improvements in dialysis techniques, and different attitudes towards the initiation of dialysis have influenced treatment goals and, consequently, dialysis prescription. However, in clinical practice prescription of dialysis still often follows a “one size fits all” rule, and there is no agreed distinction between treatment goals for the younger, lower-risk population, and for older, high comorbidity patients. In the younger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 182 publications
(276 reference statements)
0
20
0
Order By: Relevance
“…Giorgina Barbara Piccoli et. al have explained about which hemodialysis process should have higher efficiency in younger and older patients [9]. The authors have shown priority in nutrition level.…”
Section: Paper Surveymentioning
confidence: 99%
“…Giorgina Barbara Piccoli et. al have explained about which hemodialysis process should have higher efficiency in younger and older patients [9]. The authors have shown priority in nutrition level.…”
Section: Paper Surveymentioning
confidence: 99%
“…However, the risk of depletion of important nutrients during dialysis sessions with highly permeable membranes cannot be ruled out, and, while the advantages of better depuration are clear in young, well-nourished patients, it is still far from certain that high flow hemodiafiltration produces advantages for malnourished patients [26][27][28][29][30][31][32][33].…”
Section: Lipidsmentioning
confidence: 99%
“…Moreover, dialysis prescription varies widely, and very different treatments may be gathered under the same name; information on the dialysis schedule is often incomplete, thus making comparisons and implementing strategies can be challenging [29][30][31].…”
Section: Mia: Malnutrition Inflammation Atherosclerosis Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…The modest gain in efficiency (usually estimated as less than 20%) is in fact attainable only in patients with concomitant high blood flow, and even in such cases the clinical advantage may be dubious [66][67][68][69][70][71]. At present the balance may point towards a lower dialysate flow in elderly patients with low metabolic needs, where optimal dialysis is probably a compromise between depuration and depletion [72,73].…”
mentioning
confidence: 99%